Pelatihan Manajemen Karir Dalam Industri Musik Bagi Musisi Lokal Di Kota Tegal - Febri Yoga Sapta Raharjo; Faiz Irsyad Prasetyo (AMMA : Jurnal Pengabdian Masyarakat, 2024)
This program aims to enhance the competencies of local musicians in Kota Tegal in managing their careers and talents within the increasingly competitive music industry. The program is motivated by the challenges faced by local musicians, such as a lack of understanding of career management, personal branding, and how to maximize the economic value of their musical works. The program is designed as a training course consisting of four intensive sessions over two meetings, involving 20 music practitioners in Kota Tegal. The material covers career management, the role of band managers, music publishers, music distribution, music monetization, and digital marketing strategies in the music industry. The program is expected to provide participants with practical knowledge and skills to develop their careers in a more professional and structured manner. The main output of the program is the increased understanding and skills of participants in career management, which is expected to support the sustainability of local musicians' careers in Kota Tegal. Additionally, this program is anticipated to contribute to building a creative ecosystem in Kota Tegal by strengthening the capacity of local musicians to face challenges in the music industry.